2000
DOI: 10.1007/s002689910020
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Results of Total Adrenalectomy for Cushing's Disease

Abstract: The objective of this study was to present the long-term results of total adrenalectomy for Cushing's disease. Forty-four patients undergoing total adrenalectomy for Cushing's disease between 1953 and 1989 at Leiden University Medical Center, The Netherlands, were studied retrospectively. Remission was achieved in 42 patients (95%), with a mean duration of 19 years. Adrenal remnants were observed in 12 patients (27%), and were without clinical consequence in the majority of patients, but caused early recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
2
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 23 publications
6
118
2
6
Order By: Relevance
“…For some tumours (although not microadenomas), pre-TBA urinary cortisol serves as a useful marker of corticotrophinoma tumour size and functionality, and may be a useful predictor of the subsequent Nelson's syndrome development (3,33,40). However, the evidence is not conclusive, and a correlation between urinary cortisol levels and the risk of subsequent development of Nelson's syndrome has not been demonstrated in some studies (13,30,32).…”
Section: High Urinary Cortisolmentioning
confidence: 77%
See 4 more Smart Citations
“…For some tumours (although not microadenomas), pre-TBA urinary cortisol serves as a useful marker of corticotrophinoma tumour size and functionality, and may be a useful predictor of the subsequent Nelson's syndrome development (3,33,40). However, the evidence is not conclusive, and a correlation between urinary cortisol levels and the risk of subsequent development of Nelson's syndrome has not been demonstrated in some studies (13,30,32).…”
Section: High Urinary Cortisolmentioning
confidence: 77%
“…Suboptimal or absent steroid replacement therapy post TBA may increase the risk of developing Nelson's syndrome (41,42) or even result in transformation of a pre-existing adenoma into a more aggressive tumour subtype (3,26). However, most studies have not shown this (3,13,32).…”
Section: Insufficient Exogenous Steroid Replacement Therapy Post Tba mentioning
confidence: 88%
See 3 more Smart Citations